2012
DOI: 10.1039/c2nj40338b
|View full text |Cite
|
Sign up to set email alerts
|

New potential prodrugs of aciclovir using calix[4]arene as a lipophilic carrier: synthesis and drug-release studies at the air–water interface

Abstract: Two tetra-p-tert-butyl-calix [4]arene species bearing one or two anti-HSV aciclovir units tethered via carbodiester linkages at the lower rim were synthesized as possible antiviral prodrugs. The amphiphilic properties of these derivatives were studied using Langmuir balance at the air-water and air-carbonate buffer interfaces; the monolayers formed were stable on both subphases. Monolayers formed with these molecules on a carbonate buffer subphase at pH 10 and 37 1C were then used for monitoring hydrolysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…17,[21][22][23] Drug delivery and solubilization using calix[n]arenes or calix [4]resorcinarenes have been reported. [24][25][26][27][28][29][30][31][31][32][33][34][35][36][37][38] However, the use of calixarenes and calixresorcinarenes as drug delivery is still a relatively novel concept, and the number of experimental or computational studies reported so far is relatively low, despite that these macrocyclic compounds possess several advantages such as ease of synthesis and modification and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…17,[21][22][23] Drug delivery and solubilization using calix[n]arenes or calix [4]resorcinarenes have been reported. [24][25][26][27][28][29][30][31][31][32][33][34][35][36][37][38] However, the use of calixarenes and calixresorcinarenes as drug delivery is still a relatively novel concept, and the number of experimental or computational studies reported so far is relatively low, despite that these macrocyclic compounds possess several advantages such as ease of synthesis and modification and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] With such properties, calixarenes have been used in detecting metallic ions, such as alkaline [6][7][8] and alkaline earth [8][9][10] metals, cadmium, [10][11][12] copper, 7,13,14 and for incorporating neutral molecules, [15][16][17][18][19][20] including dopamine, 15 volatile organic compounds 16 and aminoacids. 17 They have also been studied in biological membranes, [18][19][20] and in the formation of molecularly organized films using self-assembled monolayers [21][22][23] and LangmuirBlodgett (LB) [6][7][8][9][10][11][12][13][15][16][17][18][19][20] techniques. These organized films have been applied in metal ion sensors, biosensors, immunosensors and for encapsulating nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Due to their cone-like structure [1][2][3] and the presence of phenol oxygen donor atoms, [1][2][3][4] calixarenes may be complexed with metal ions or incorporate charged and neutral molecules. [1][2][3][4][5] With such properties, calixarenes have been used in detecting metallic ions, such as alkaline [6][7][8] and alkaline earth [8][9][10] metals, cadmium, [10][11][12] copper, 7,13,14 and for incorporating neutral molecules, [15][16][17][18][19][20] including dopamine, 15 volatile organic compounds 16 and aminoacids. 17 They have also been studied in biological membranes, [18][19][20] and in the formation of molecularly organized films using self-assembled monolayers [21][22][23] and Langmuir-Blodgett (LB) [6][7][8][9][1...…”
Section: Introductionmentioning
confidence: 99%
“…The calixarenes used in the present study (Figure ) have one or two nalidixic arms linked to the lower rim of the of p - tert -butylcalix[4]arene platform via a carboxylate function present in the quinolone moiety. Their interfacial and complexation properties were studied before. …”
Section: Introductionmentioning
confidence: 99%